Hodnocení finanční situace podniku a návrhy na její zlepšení - Logara, Vanja (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Vypracovaná finanční analýza je zaměřena na odhalení silných a slabých stránek podniku. Bakalářská práce se zabývá provedením finanční analýzy společnosti Lino s.r.o. a na základě výsledků a jejich vyhodnocení jsou uvedena doporučení vedoucí ke zlepšení stávající situace firmy.

The elaborated financial analysis is focussed on detection of weak and strong points of the company. The bachelor thesis discusses implementation financial analysis of company Lino s.r.o.. On the basis on results of the undertaken analysis and these are going to lead to improvement of current economic situation of the firm.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční situace; marketing; SWOT analýza; finanční ukazatele; Financial situation; marketing; SWOT analyse; financial indexes